2015
DOI: 10.1134/s0006297915090084
|View full text |Cite
|
Sign up to set email alerts
|

Low concentrations of hydrogen peroxide activate the antioxidant defense system in human sperm cells

Abstract: The effect of low concentrations of hydrogen peroxide (10-100 µM) on sperm motility and on the activity of the sperm enzyme glyceraldehyde-3-phosphate dehydrogenase (GAPDS) was investigated. Incubation of semen samples with 10 and 100 µM hydrogen peroxide increased the content of spermatozoa with progressive motility by 20 and 18%, respectively, and enhanced the activity of GAPDS in the sperm cells by 27 and 20% compared to a semen sample incubated without additions. It was also found that incubation with 10 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…While hydrogen peroxide is the most widely used substance to induce oxidative stress in sperm cultures in vitro [27,28], it has been shown that FeAA could act as an effective OS-promoting agent in mammalian spermatozoa [22,23,24]. The substance takes advantage on the specific characteristics of iron as a transition metal, thus, providing an appropriate environment for the Fenton and Haber-Weiss reaction [29] leading to oxidative degeneration of lipids, DNA and proteins [30].…”
Section: Discussionmentioning
confidence: 99%
“…While hydrogen peroxide is the most widely used substance to induce oxidative stress in sperm cultures in vitro [27,28], it has been shown that FeAA could act as an effective OS-promoting agent in mammalian spermatozoa [22,23,24]. The substance takes advantage on the specific characteristics of iron as a transition metal, thus, providing an appropriate environment for the Fenton and Haber-Weiss reaction [29] leading to oxidative degeneration of lipids, DNA and proteins [30].…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 is one of the most damaging reactive oxygen species (ROS) to human spermatozoa, and its impact on sperm motility has been extensively reported [28,29]. Human ejaculated spermatozoa were exposed to different concentrations of H 2 O 2 (120, 600, and 1200 µM) and motility parameters and viability were assessed after 2 h, 15 min, and 30–60 sec, respectively (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported that incubation of sperms with low concentrations of H 2 O 2 increases the amount of glutathione (GSH) in the sperm cells. Finally, accumulation of GSH increases the GAPDS activity and consequently improves sperm motility [25].…”
Section: Discussionmentioning
confidence: 99%
“…As already mentioned, Vit.D3 increased OS in this study, which is contradictory to prior studies and there are two possible reasons for this phenomenon: One is that this dose of vitamin D3 does not have an antioxidant effect on sperm cells because its effect is dose dependent [24] and sperm is a sensitive cell with many polyunsaturated fatty acids in the plasma membrane and a small antioxidant mechanism in the cytoplasm [26]. The other possibility is that the increase in OS was small and had a positive effect on sperm cells, as one study has reported that low level of H 2 O 2 can improve sperm motility by increasing GAPDS protein activity [25] and another study has shown that middle and high concentrations of H 2 O 2 disrupt sperm motility due to a decrease in GAPDS activity [27]. Although GAPDS activity was not assessed in this study, the second possibility is more acceptable since sperm motility was in fact increased in the present study.…”
Section: Discussionmentioning
confidence: 99%